Electoral Competition under Media Influence - Wolfgang Bräuer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
We suggest a model of electoral competition between two parties which is extended by a third player : mass media. The classical one-dimensional competition model is changed by introducing an issue-specific sensibility-coefficient and by allowing for non-voting. The winner is selected by majority rule. The voter potentials of the parties are determined by their current policy choice. Deviating from (exogenous) traditional party policy reduces the credibility of a party in the eyes of potential voters. The number of non-voters increases with the sensibility of individuals to the issue and with the deviation distance. By reporting with political bias, mass media has selective influence on the sensibility-coefficient of potential voters of both parties. They get either desensitised or over-sensitised in respect to party credibility which alters the number of non-voters. Parties being able to successfully communicate with mass media can manage to turn an unfavourable situation before election campaigning into an electoral victory.
Keywords: D82; D72; C72; 330; Public choice; electoral competition; mass media; reputation; credibility